Alternating Offers in Economic Environments - Harold Houba (Tinbergen Institute, 2005)
The Nash bargaining solution of a modified bargaining problem in the contract space yields the pair of stationary subgame perfect equilibrium proposals in the alternating offers model, also for positive time between proposals. As time vanishes, convergence to the Nash bargaining solution is immediate by the Maximum Theorem. Numerical implementation in standard optimization packages is straightforward.
Keywords: C72; C73; C78; 330; Bargaining; Negotiation; Alternating offers; subgame perfect equilibrium; Nash bargaining solution; Maximum Theorem; Applied General Equilibrium; Verhandlungstheorie; Nash-Gleichgewicht; Dynamisches Spiel; Theorie; Nichtkooperatives Spiel